Dose selection for fremanezumab (AJOVY) phase 3 pediatric migraine studies using pharmacokinetic data from a pediatric phase 1 study and a population pharmacokinetic modeling and simulation approach. (September 2021) - Cohen-Barak, Orit; Radivojevic, Andrijana; Jones, Aksana; Fiedler-Kelly, Jill; Gillespie, Michael; Brennan, Michael; Gutman, Dikla; Rasamoelisolo, Michele; Hallak, Hussein; Loupe, Pippa; Kessler, Yoel; Ning, Xiaoping; et al.
Background: Potential fremanezumab doses for pediatric patients were evaluated using pharmacokinetic modeling and simulation. An open-label phase 1 pharmacokinetic and safety study was conducted in pediatric patients with migraine. This study's results together with refinement of the adult population pharmacokinetic model were used to determine fremanezumab dose recommendations for phase 3 pediatric studies. Methods: Initial application of the adult model suggested that a 75 mg dose in pediatric patients would match exposures determined safe and efficacious in adults; thus, in the phase 1 study, 15 patients, aged 6–11 years and weighing 17–45 kg received a single subcutaneous 75 mg fremanezumab dose. The sparse pharmacokinetic data collected were used to refine the adult model and simulate concentration-time profiles for monthly subcutaneous doses (60 to 225 mg) in a virtual pediatric population. Results: In the phase 1 pediatric study, the safety profile was similar to that of adults. A two-compartment model with first-order absorption and elimination and body weight effects on clearance and central volume was found to adequately describe the pediatric pharmacokinetic data. Conclusions: Using exposure matching to the effective adult fremanezumab dose (225 mg subcutaneous monthly), modeling and simulations predict recommended dose of 120 mg in pediatric patients weighing < 45 kg. Registration: The phase 1 study of this report is registered at EudraCT with the identifier 2018-000734-35.